Acute intestinal obstruction: small intestine vs. large intestine: an analysis - Sharma, Latika; Srivastava, Harshit; Pipal, Dharmendra Kumar; Kothari, Saurabh; Dhawan, Rohit; Purohit, Poojan M. (International Surgery Journal, 2017)
Background: Bowel obstruction is one of the most common causes of acute abdomen and also a common surgical emergency.The causes of IO vary significantly depending on geographical location. The aim of this study was to identify the etiology, clinical presentation, management and outcomes of patients with acute mechanical IO presenting in Jodhpur, Rajasthan. Methods: A prospective study was conducted at Mahatma Gandhi Hospital and Mathura Das Mathur Hospital (associated with Dr. SN Medical College), Jodhpur, Rajasthan. 100 patients with acute intestinal obstruction were admitted and evaluated. Blood routine, X-Ray abdomen, USG abdomen and CECT (if required) were done. A pre-operative diagnosis was made. Intra-operative findings and Post-operative complications were noted and follow up was done till the patient was discharged from the hospital. Results: A total of 69 male and 31 female patients, presented with acute mechanical IO during the period of the study. Mean patient age was 48.5 years with peak incidence in those aged 31-45 years. The foremost signs and symptoms were abdominal distension (88%), obstipation (87%), abdominal pain (81%) and nausea/ vomiting (47%). Adhesions and bands (29%), hernia (13%), neoplasm (9%) and pseudo-obstruction (8%) were the leading causes of intestinal obstruction. The sensitivity of X-ray and USG in present study was 67% and 75% respectively. Most common complication associated was wound infection (17%) followed by paralytic ileus (7%) and respiratory tract infections (6%). Late presentation was associated with poor prognosis. 4 patients expired before surgery. Post-operative mortality was associated with 6 patients and was more common in cases which presented with gangrenous bowel. Conclusions: The most common causes of IO in this study were adhesions and bands, hernia, neoplasm and pseudo-obstruction. Presence of bowel gangrene was associated with higher morbidity and mortality.